2009
DOI: 10.1002/ijc.24585
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the carcinogen 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK) in smokers from 3 populations with different risks of lung cancer

Abstract: Native Hawaiian smokers are at higher risk and Japanese-American smokers at lower risk of lung cancer (LC), compared with white smokers, even after accounting for smoking history. Because variation in carcinogen exposure/metabolism may occur separately of smoking amount, we compared urinary biomarkers of uptake and detoxification of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)-a potent lung carcinogen-among 578 smokers in these ethnic/racial groups in Hawaii. We measured the NNK metabolite 4-(methylnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…One of the most extensively investigated TSNAs in tobacco products is NNK (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone), a potent carcinogen that is metabolized in the liver to form NNAL (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanonol) [2,3]. NNAL concentrations within subjects have been associated with a higher risk for developing lung cancer among smokers, indicating its use as a biomarker of lung cancer risk among smokers [4,5]. While research has extensively associated secondhand smoke (SHS) concentrations with particulate matter less than 2.5 microns (PM 2.5 ) and human biomarkers, the impact of occupational exposure to SHS in semiopen cafes and TSNA uptake remains relatively unexplored [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most extensively investigated TSNAs in tobacco products is NNK (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone), a potent carcinogen that is metabolized in the liver to form NNAL (4-(methylnitrosamino)-1-(3-pyridyl)-1-butanonol) [2,3]. NNAL concentrations within subjects have been associated with a higher risk for developing lung cancer among smokers, indicating its use as a biomarker of lung cancer risk among smokers [4,5]. While research has extensively associated secondhand smoke (SHS) concentrations with particulate matter less than 2.5 microns (PM 2.5 ) and human biomarkers, the impact of occupational exposure to SHS in semiopen cafes and TSNA uptake remains relatively unexplored [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Derby et al (2009) found in a study of Native Hawaiian, White, and Japanese American smokers that racial differences were seen in the relationship between CPD and urine NNAL, but these racial differences were eliminated when the relationship between urine nicotine equivalents and NNAL was examined. Roethig et al (2009) reported a strong correlation between urine nicotine equivalents and urine NNAL but did not compare the relationship between CPD and urine NNAL.…”
Section: Relationship Between Nicotine Intake and Exposure To Tobaccomentioning
confidence: 99%
“…For example, NNK-induced miRNA changes should been studied in lung cancer models [147][148][149]. A whole genome and transcriptome analysis should be performed in NNK-induced lung cancers, which will provide information of a new paradigm of mechanism of NNK-induced carcinogenesis, and help to explain the differences of lung cancer risk among different individuals and populations [150][151][152]. In addition, these NNK-induced lung cancer animal models should be further improved because of their relatively long latency.…”
Section: Conclusion and Perspectives On Future Researchmentioning
confidence: 99%